Soldagem por fricção e mistura (FSW) no aço inoxidável austenítico AISI 304 - Plaine, Athos Henrique (2013)
Stainless steels are an important class of engineering materials with attractive properties such as high mechanical and corrosion resistance and thereby widely used in a variety of industries and environments due to its outstanding properties such as mechanical and corrosion resistance. These materials, which are usually considered difficult to weld by conventional fusion welding processes, have demonstrated outstanding performance when joined by Friction Stir Welding (FSW), a solid-state joining process. FSW input energy regulates the magnitude of the thermal cycle and the intensity of deformation during the process, and it can be controlled by the welding parameters, which affects the grain features and consequently the mechanical properties of the joints. The aim of this work is to evaluate the feasibility of producing friction stir welds of a 304 austenitic stainless steel and correlate this process to the microstructures and mechanical properties in these joints. The samples were produced using a polycrystalline cubic boron nitrides (PCBN) tool and four different rotational speeds. Microstructural investigation showed that all joints presented, besides the base material (BM), the three typical FSW zones: stir zone (SZ), termomecanically affected zone (TMAZ) and heat affected zone (HAZ). The ZTA exhibited a microstructure similar to MB, while ZTMA and ZM were characterized by dynamic recovery and recrystallization, respectively. In the advancing side of ZM was observed the formation of sigma phase, a brittle and undesirable phase. The welding parameters variation affected mainly the deformation experienced by the material, the average grain size and length of the weld zones. The mechanical tests were consistency with the observed microstructures, being the mechanical properties of joints higher than BM, which is very attractive from the technological point of view.